Case report: A rare combination of right aortic arch with right patent ductus arteriosus and right tracheal bronchus causing impaired respiratory function - Lian, Xingchen; Wang, Ning; Bai, Chuan; Wen, Ping; Liu, Yuhang (Frontiers in Cardiovascular Medicine, 2022)
A right aortic arch with concomitant right patent ductus arteriosus and right tracheal bronchus is a rare congenital anomaly. Herein, the respiratory and circulatory functions of the child were normal at early ages, and imaging examination indicated that conservative treatment was suitable. However, with the growth and development of the child, the right tracheal bronchus was oppressed by the right arterial duct. We performed a cut and ligation of the right patent ductus arteriosus to relieve the pressure on the right tracheal bronchus. At the 6-month follow-up, the child had recovered well and exhibited no symptoms of respiratory restriction. Therefore, we believe that early interventions should be considered for this rare anatomic presentation to benefit the patient’s respiratory and circulatory system. Our experience provides a foundational reference for future cases.